2014
DOI: 10.1534/genetics.114.164012
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin FG Domains Facilitate mRNP Remodeling at the Cytoplasmic Face of the Nuclear Pore Complex

Abstract: Directional export of messenger RNA (mRNA) protein particles (mRNPs) through nuclear pore complexes (NPCs) requires multiple factors. In Saccharomyces cerevisiae, the NPC proteins Nup159 and Nup42 are asymmetrically localized to the cytoplasmic face and have distinct functional domains: a phenylalanine-glycine (FG) repeat domain that docks mRNP transport receptors and domains that bind the DEAD-box ATPase Dbp5 and its activating cofactor Gle1, respectively. We speculated that the Nup42 and Nup159 FG domains pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 82 publications
2
49
0
Order By: Relevance
“…6D; Extended Data Fig. 9C), consistent with the known role of FxFG/FG-type repeats in docking exporting RNAs 31 . In contrast, the GLFG-type repeats are enriched in regions adjacent to the inner ring and near the cytoplasmic entrance to the central channel.…”
Section: Resultssupporting
confidence: 80%
“…6D; Extended Data Fig. 9C), consistent with the known role of FxFG/FG-type repeats in docking exporting RNAs 31 . In contrast, the GLFG-type repeats are enriched in regions adjacent to the inner ring and near the cytoplasmic entrance to the central channel.…”
Section: Resultssupporting
confidence: 80%
“…Our prior studies revealed a role for the FG domain in recruiting the mRNP to be in proximity to Gle1 and Dbp5 for remodeling 28 , via the Nup42 FG domain interacting with Mex67-Mtr2 (Figure 1B) 29 . In fact, a fusion between Gle1 and the FG domain of Nup42 (gle1-FG nup42 ) bypasses the requirement for Nup42 in some genetic contexts 28 . The Nup42 CTD is also required for specific functions.…”
Section: Introductionmentioning
confidence: 86%
“…Nup42/hNup42 mediates the export of heat shock transcripts 22,30 , and deletion of NUP42 together with IPK1 , the kinase that produces IP 6 , results in a temperature sensitive mRNA export defect 31 . Nup42 CTD expression is sufficient for the function in heat shock mRNA export 32 and rescues nup42△ ipk1△ temperature sensitivity 31 ; whereas, expression of the gle1-FG nup42 fusion does not restore these defects in nup42△ mutants 28 . Since proper Gle1 and Dbp5 function are likewise required for heat shock mRNA export 30,33 , and IP 6 is required for normal Gle1 regulation of Dbp5, we propose that the Nup42 CTD might also impact their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…9,36 This asymmetry is required for aspects of NPC function, especially mRNA export, which relies on the cytoplasmically biased Nup82 complex for messenger ribonucleoproteins (mRNPs) remodeling before release into the cytoplasm for translation by ribosomes. 15,37 There are significant differences between opisthokont and trypanosome FG-motif domain sequences, making it near impossible to identify orthologs of opisthokont FG-Nups in trypanosomes by in silico means alone. However, through affinity capture, we were able to identify orthologs of FG-Nups, based on the core scaffold structure with which they associate.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…40 A major source of Nup asymmetry in opsithokonts is the exclusively cytoplasmic ScNup82/HsNup88 subcomplex, tethering specialized FG-Nups that provide the interaction platform for factors critical for mRNA export. 15,37 However, TbNup76, the presumed trypanosome ortholog of ScNup82, is located on both the cytoplasmic and nucleoplasmic faces of the trypanosome NPC. 5 Herein lies another cautionary tale of making sure that one does not assume that, just because proteins are orthologous, they function in the same way in organisms that are evolutionarily distant.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%